DIGITAL MARKETING AS A TOOL FOR STIMULATING SALES THROUGH PRODUCT PACKAGING: RESULTS OF A NEUROMARKETING STUDY - BORYSOVA, Tetiana; HALKO, Ludmyla; DUDAR, Volodymyr (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The study presents the results of research conducted by the authors in the Neuromarketing and Advertising Laboratory at the West Ukrainian National University. An analysis of scientific publications revealed a lack of comprehensive exploration into the impact of visual characteristics of product packaging in the context of online sales. The aim of the article was to identify the features of consumer perception of packaging in the online environment and to evaluate its influence on purchase decision-making within the framework of internet marketing communication. The following methods were employed: content analysis of advertising materials; neuromarketing testing using eye-tracking technology; questionnaire surveys; statistical analysis; comparative analysis; and synthesis. The study revealed the following findings. First, the use of red as a visual trigger is advisable, as this color demonstrated the highest levels of engagement, fixation, and recall accuracy across all age and gender groups. Second, segmenting packaging design in online communication by age preferences is justified, since the data indicate clearly defined color preferences among age groups: younger consumers tend to favor bright and emotionally charged colors, whereas older respondents (aged 36–55) prefer more subdued and reliable tones. Third, enhancing packaging design with the use of video and 3D animations shows significant potential for increasing online sales. Fourth, the color palette functions as a powerful branding element in the digital environment, as such “color-driven” communication fosters the formation of brand associations. Fifth, visually oriented packaging should appear on screen within the first three seconds of an advertisement. Sixth, packaging design should be adapted to gender-based preferences in online advertising, as women demonstrated higher visual engagement with emotionally associated colors, while men responded more to functional ones. The research results enabled the development of practical recommendations for improving packaging design as a tool to enhance the effectiveness of internet marketing and sales, as well as for refining neuromarketing strategies.